Translation and validation of the polish version of the self-reported postural awareness scale in an adult sample - Agnieszka Jankowicz-Szymańska; Katarzyna Wódka; Aneta Grochowska; Anna Stefanowicz-Kocoł; Mirela-Ioana Bilc; Dennis Anheyer; Urszula Kozioł; Holger Cramer; Adam Sagan (Frontiers in Psychology)
IntroductionBody awareness has gained increasing attention in research as a crucial link between psychological and somatic processes, offering tangible benefits for physical health and well-being. This study aimed to validate and culturally adapt the Polish version of the Postural Awareness Scale (PAS) in adults aged 20–70.MethodsThe relationships between the two PAS subscales: Ease/Familiarity with Postural Awareness and Need for Attention Regulation with Postural Awareness, and chronic stress levels (measured by the Perceived Stress Scale, PSS-10), as well as gender, age, and family status (individuals in permanent relationships versus singles), were explored. The factor structure was tested by exploratory and confirmatory factor analysis.Results and discussionA total of 333 healthy participants (mean age: 36.74 ± 19.7 years; 76% female) completed the study. Cultural adaptation of the PAS required the removal of one item, resulting in an 11-item Polish version with strong internal consistency (Crohnbach’s α: 0.80–0.82) and psychometric properties comparable to the original German version. Multi-group analyses confirmed metric equivalence of the scale across age, gender, and family status. A negative correlation was observed between PAS scores and perceived stress (PSS-10), while no significant associations were found with gender or family status. Older participants exhibited higher scores on the Ease/Familiarity with Postural Awareness subscale. These findings suggest that the Polish version of the PAS is a reliable and valid tool for assessing postural awareness in diverse adult populations, with potential applications in research and clinical practice.